The Time-Course of Sentence Meaning Composition. N400 Effects of the Interaction between Context-Induced and Lexically Stored Affordances - Cosentino, Erica; Baggio, Giosuè; Kontinen, Jarmo; Werning, Markus (Frontiers in Psychology, 2017)
Contemporary semantic theories can be classified along two dimensions: (i) the way and time-course in which contextual factors influence sentence truth-conditions; and (ii) whether and to what extent comprehension involves sensory, motor and emotional processes. In order to explore this theoretical space, our ERP study investigates the time-course of the interaction between the lexically specified telic component of a noun (the function of the object to which the noun refers to, e.g., a funnel is generally used to pour liquids into containers) and an ad-hoc affordance contextually induced by the situation described in the discourse. We found that, if preceded by a neutral discourse context, a verb incongruent with the noun’s telic component as in “She uses the funnel to hang her coat” elicited an enhanced N400 compared to a congruent verb as in “She uses the funnel to pour water into a container”. However, if the situation introduced in the preceding discourse induced a new function for the object as an ad-hoc affordance (e.g., the funnel is glued to the wall and the agent wants to hang the coat), we observed a crossing-over regarding the direction of the N400 effect: comparing the ad-hoc affordance-inducing context with the neutral context, the N400 for the incongruent verb was significantly reduced, whereas the N400 for the congruent verb was significantly enhanced. We explain these results as a consequence of the incorporation of the contextually triggered ad-hoc affordance into the meaning of the noun. Combining these results with an analysis of semantic similarity values between test sentences and contexts, we argue that one possibility is that the incorporation of an ad-hoc affordance may be explained on the basis of the mental simulation of concurrent motor information.